2016
DOI: 10.1093/ageing/afw208
|View full text |Cite
|
Sign up to set email alerts
|

Inequalities in receipt of mental and physical healthcare in people with dementia in the UK

Abstract: BackgroundUK Dementia Strategies prioritise fair access to mental and physical healthcare. We investigated whether there are inequalities by deprivation or gender in healthcare received by people with dementia, and compared healthcare received by people with and without dementia.Methodswe investigated primary care records of 68,061 community dwelling dementia patients and 259,337 people without dementia (2002–13). We tested hypotheses that people with dementia from more deprived areas, and who are women receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 30 publications
3
53
1
Order By: Relevance
“…13 This model appears to have been widely adopted, 27 but navigating the complex health and social care system after diagnosis remains an obstacle to effective care and support, 5,12 and people with dementia have recently been shown to receive less primary preventative health care than people without dementia. 28 In fact, dementia advisers were never intended to provide intensive support at the level offered by specialist services, such as Admiral Nurses, 13 and qualitative evidence suggests that there continues to be a demand for a more intensive approach. 24 Indeed, a systematic review of case-management programmes for people with dementia 29 concluded that the intensity of case management interventions was one of two factors determining the magnitude of their effects, the other being the integration level of the system in which the case managers worked.…”
Section: The Need For the Researchmentioning
confidence: 99%
“…13 This model appears to have been widely adopted, 27 but navigating the complex health and social care system after diagnosis remains an obstacle to effective care and support, 5,12 and people with dementia have recently been shown to receive less primary preventative health care than people without dementia. 28 In fact, dementia advisers were never intended to provide intensive support at the level offered by specialist services, such as Admiral Nurses, 13 and qualitative evidence suggests that there continues to be a demand for a more intensive approach. 24 Indeed, a systematic review of case-management programmes for people with dementia 29 concluded that the intensity of case management interventions was one of two factors determining the magnitude of their effects, the other being the integration level of the system in which the case managers worked.…”
Section: The Need For the Researchmentioning
confidence: 99%
“…8,9 Timely diagnosis is essential for getting support, optimising safety and making choices about future care while the person with dementia retains the ability to participate in decision-making. 10,11 Whereas higher deprivation is a barrier to dementia services and treatment in other Western countries, 12,13 data from the United Kingdom are conflicting [14][15][16] and not detailing the South Asian minority. Qualitative literature has shown that barriers to timely diagnosis of dementia in older South Asian adults may include language, health beliefs, carers' attitudes, stigma and lack of cross-cultural adaptation of services.…”
Section: Introductionmentioning
confidence: 99%
“…Since the indices for area deprivation have been widely associated with inequalities in access to care and services, people with dementia living in deprived areas might have limited support from local health and social care systems. Recent analyses of UK primary care data suggested that people with dementia in least deprived areas were 25% more likely to be prescribed antidementia drugs such as cholinesterase inhibitors and memantine than the most deprived but did not find any variation in receipt of healthcare and psychotropic medication across deprivation levels . On the other hand, Dementia Atlas, an interactive website developed to monitor indicators for primary, secondary, and tertiary care in England, reveals disparity of care and different completion rates of the annual care review across areas .…”
Section: Discussionmentioning
confidence: 99%
“…The association between deprivation quintiles and living well indicators in people with dementia Quality of Life in Alzheimer's Disease Scale; SwLS, Satisfaction with Life Scale; WHO-5, World Health Organization Five Well-being Index; P, P-value of Wald test.Accounting for country and imputed for missing data, N = 1547. more likely to be prescribed antidementia drugs such as cholinesterase inhibitors and memantine than the most deprived 12 but did not find any variation in receipt of healthcare and psychotropic medication across deprivation levels 29. On the other hand, Dementia Atlas, an interactive website developed to monitor indicators for primary, secondary, and tertiary care in England, reveals disparity of care and different completion rates of the annual care review across areas.…”
mentioning
confidence: 92%